ACQUITTAL IN PAKISTAN: NAVIGATING THE LEGAL REALITIES AND PUBLIC SENTIMENTS (Contemporary Journal of Social Science Review, 2025)
This paper examines high of acquittal in Pakistan’s criminal justice system, legal realities and public sentiments. The research includes qualitative interviews with legal professionals i.e. Judges from District Judiciary, Public Prosecutors, Lawyers dealing with criminal cases and legal Inspectors/DSPs serving in police department along with doctrinal analysis. Analysis has been characterized by key issues comprise of procedural deficiencies, inconsistent judicial decision making characterized influence of political and personal biases, poor investigations and limited use of forensic evidence. Accordingly, the research seeks for  all reforms  inclusive specialized jurisdiction for judicial officers, clear sentencing guidelines, increased forensic capability, and improved investigative capability in order to reduce acquittals and improve public trust. The result emphasizes the requirement for system wide modernization to get to grips with these systemic problems, in order to provide fair, timely and consistent justice.